Psychometric Properties of the Interpersonal Needs Questionnaire-15 in Spanish Adolescents - Pérez Rodríguez, Sandra; García-Alandete, Joaquín; Gallego Hernández de Tejada, Blanca; Guillén, Verónica; Marco, Jose Heliodoro (Frontiers in Psychiatry, 2022)
Background: Thwarted Belongingness (TB) and Perceived Burdensomeness (PB) are considered risk factors of suicide behavior in the Interpersonal Theory of Suicide and constitute the main factors of the Interpersonal Needs Questionnaire – INQ. Aims: The present study analyzes the internal consistency, construct validity, and invariance across sex and age of the INQ-15, which comprises two subscales, in a sample of Spanish community adolescents. Methods: Participants were 1536 adolescents from 12 to 19 years old. The INQ-15, the total number of non-suicidal self-injuries (NSSI), the Hopelessness Scale, and the Purpose in Life Test‐Adolescents (PIL-A) were used. Results: The INQ-15 showed good internal consistency for TB (ϖ = .88) and PB (ϖ = .78) subscales and construct and concurrent/discriminant validity in the whole sample. Both the the PB and TB subscales showed a good fit (SBχ²(9) = 6.448, p = .694, CFI = 1.000, RMSEA = .000 (90% CI [.000, .022]) and SBχ²(27) = 248.973, p = .000, CFI = .922, RMSEA = .073 (90% CI [.065, .082]) respectively. Regarding the invariance analyses, we found (1) non-invariance in the PB subscale across sex groups and metric, scalar, and stric invariance across age groups, and (2) that it was not possible to perform the invariance analysis for the TB subscale across both sex and age because the fit was not adequate for both boys and 12-15 years old groups. Positive and significant relationships were found between the INQ-15 subscales and hopelessness and NSSI frequency, and negative and significant correlations with meaning in life. Conclusions: The INQ-15 is a valid instrument for assessing TB and PB in Spanish adolescents. Future studies should analyze the invariance of this instrument in adolescents across sex and age.